2005
DOI: 10.1080/00365520510011588
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of surgically and medically treated patients with gastroesophageal reflux disease: A matched-pair follow-up study

Abstract: The study shows that in our area anti-reflux surgery is more effective in relieving reflux symptoms than medical care according to clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 26 publications
3
12
1
2
Order By: Relevance
“…Moreover, we found that 19.4 % of patients who had undergone the procedure were taking antireflux drugs occasionally. This percentage is similar to that previously reported [16]. We could not obtain a specific utility and incorporate these results into our model given the format of our study.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, we found that 19.4 % of patients who had undergone the procedure were taking antireflux drugs occasionally. This percentage is similar to that previously reported [16]. We could not obtain a specific utility and incorporate these results into our model given the format of our study.…”
Section: Discussionsupporting
confidence: 78%
“…In 2002, we performed a 3-10 years follow-up study of patients with GERD treated with fundoplication, and matched non-operated controls that had been treated with anti-reflux medications, according to clinical practice in our region [18]. In contrast to the similar results of medical and surgical treatments that have been found in prospective controlled studies [19], we found that operated patients reported significantly less heartburn/acid regurgitation than their non-operated controls.…”
Section: Specialmentioning
confidence: 83%
“…All patients were recruited because they were responders in a follow-up questionnaire study one-and-a-half years earlier, focusing on gastroenterological symptoms and health-related quality of life [18]. Indications for surgery were according to clinical practice in our two hospitals.…”
Section: Study Groupsmentioning
confidence: 99%
“…Bei der Fundoplikation wird durch Repositionierung des unteren Ösophagussphinkters im Abdomen und Anlegen einer vollständigen oder partiellen Manschette aus Fundusanteilen des Magens um den unteren Öso-phagus die Refluxbarriere verstärkt. In kontrollierten Studien waren die Langzeitergebnisse der laparoskopischen oder offenen Fundoplikation mit denen der medikamentösen Therapie vergleichbar [13,19], gingen aber mit einer erhöhten Mortalität und Morbidität einher. Komplikationen umfassen anhaltende Schluckbeschwerden und Blähungen.…”
Section: Chirurgische Therapieunclassified